Pre-treatment plasma cytokine levels as potential predictors of short-term remission of depression. (26th November 2022) - Atake, Kiyokazu; Hori, Hikaru; Kageyama, Yuki; Koshikawa, Yosuke; Igata, Ryohei; Tominaga, Hirotaka; Katsuki, Asuka; Bando, Hiroki; Sakai, Shiho; Nishida, Keiichiro; Takekita, Yoshiteru; Kato, Tadafumi; et al.
Abstract: Objectives: The response to antidepressants varies significantly among individuals and is difficult to predict before treatment. In this randomised control trial, we explored cytokines that correlate with the therapeutic effect of mirtazapine (MIR) and selective serotonin reuptake inhibitors (SSRIs) and whether they could be predictors of remission for each antidepressant. Methods: Plasma cytokines, such as tumour necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, and granulocyte-macrophage colony-stimulating factor (GM-CSF) were assayed in 95 participants before medication and assayed by the enzyme-linked immunosorbent assay. The Hamilton Rating Scale for Depression assessed depressive symptoms over 4 weeks. Results: In the SSRI group, the baseline GM-CSF level was significantly higher in the remission group than in the non-remission group ( p  = .022). In the MIR group, the baseline level of TNF-α was significantly higher ( p  = .039) and IL-2 was lower ( p  = .032) in the remission group than in the non-remission group. In patients prescribed with MIR, the cut-off values of TNF-α (10.035 pg/mL) and IL-2 (1.170 pg/mL) calculated from the receiver operating characteristic curve suggested that the remission rate, which corresponds to a positive predictive value, could be increased from 31.3% to 60.0% and 50.0%, respectively. For those prescribed with SSRIs, the remission rate was 37.0% and using the cut-off value of GM-CSF (0.205 pg/mL), the remission rate could be almost doubled to 70%. Conclusions: Our study shows that pre-treatment plasma concentrations of TNF-α, IL-2, and GM-CSF may suggest the predictability of remission by SSRIs or MIR.